"Where Your Voice Burns Like Fire": Visual art and radio broadcasting as semiotic practices of intergenerational political socialization among the Purépecha of Cherán, México. Issue 2 (June 2021) - Wright, Anthony Gerard; José Velázquez Morales, Jurhamuti
This article analyzes visual art and radio broadcasting as semiotic practices that serve as crucial sites of child and youth participation in Indigenous social movements. Looking specifically at a movement against organized crime, political corruption, and environmental exploitation that emerged in 2011 among the Purépechan people of Cherán, Michoacán, México, we show how young people's creative practices present a significant challenge to hegemonic models of adult- directed political socialization and participation, although they do not result in a total flattening of age-based hierarchies. Drawing on multimodal ethnographic fieldwork and personal experience in the movement, we show how the creative practices of youth activists facilitate the production and circulation of visual and sonic content that conveys historical and onto-epistemological frameworks which guide the movement. We also show how the circulation of this content generates the potential to influence those who come into contact with it, including both Purépechans and non-Purépechans who reside well beyond the borders of Cherán. In doing so, we demonstrate that multimodal ethnographic attention to the ways in which young people's diverse semiotic repertoires are deployed in contexts of political activism can provide valuable insights about political socialization, intergenerational relationships, and the entanglement of a variety of politically charged semiotic forms in everyday life.